Immunotherapy of cancer - Wang, Xiang-Yang; Fisher, Paul B. (Advances in cancer research, 2019)
'Immunotherapy of Cancer, ' volume 143 in the Advances in Cancer Research series, provides invaluable information on the exciting and fast-moving field of cancer research. Contributions from leading experts in the field make this a must have update on the topic. Key Features: Provides that latest information on cancer research; Offers outstanding and original reviews on a range of cancer research topics; Serves as an indispensable reference for researchers and students alike. Readership: Researchers and students in the basic and clinical sciences of cancer biology and oncology, plus related areas in genetics, immunology, pharmacology, cell biology, and molecular biology. --